2012
DOI: 10.1093/esr/jcs044
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country Differences in Graduate Overeducation

Abstract: Cross-country differences in graduate overeducation and its persistence **We investigate the factors that contribute to the cross-country variation in graduate overeducation and its persistence by means of multi-level analysis. Our analysis is based on data from representative surveys among graduates in thirteen European countries and Japan and focuses on the jobs six months and five years after graduation. Major factors to explain the cross-country variation in overeducation and its persistence are found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(156 citation statements)
references
References 38 publications
13
141
0
2
Order By: Relevance
“…The results very clearly support the view that overeducation is predominantly driven by an excess in the supply of educated labour with the ratio between the number of graduates in employment and the share of workers in professional occupations highly significant in both equations. This is consistent with job competition and assignment approaches and with previous empirical findings (Verhaest and van der Velden, 2013;Ghignoni et al, 2014). However, the marginal effects are small with the models suggesting that a 10 % increase in this ratio will drive male and female overeducation rates up by 0.5 and 0.7 parentage points respectively.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The results very clearly support the view that overeducation is predominantly driven by an excess in the supply of educated labour with the ratio between the number of graduates in employment and the share of workers in professional occupations highly significant in both equations. This is consistent with job competition and assignment approaches and with previous empirical findings (Verhaest and van der Velden, 2013;Ghignoni et al, 2014). However, the marginal effects are small with the models suggesting that a 10 % increase in this ratio will drive male and female overeducation rates up by 0.5 and 0.7 parentage points respectively.…”
Section: Resultssupporting
confidence: 90%
“…Our approach is slightly different as we explicitly focus on factors that directly address supply and demand imbalances or mismatches, whereas, with the exception of the youth unemployment rates at NUTS 2 level, Ghignoni et al (2014) analyse demand and supply factors separately. Croce et al (2012) and Verhaest et al (2013) also found that measures related to excess supply of skilled labour were related to the incidence of overeducation.…”
Section: Labour Market Demand / Supply Indicators: Both the Job Compementioning
confidence: 95%
See 2 more Smart Citations
“…It is a developed country supporting one of the largest percentages of overeducated workers (OECD, 2013a), a feature that was also observed before the current economic crisis (OECD, 2009;andVerhaest andResearch Institute of Applied Economics Working Paper 2014/11, pàg. 5 Regional Quantitative Analysis Research Group Working Paper 2014/06, pag.…”
Section: Introductionmentioning
confidence: 98%